Sulfobacillus thermosulfidooxidans strain Cutipay enhances chalcopyrite bioleaching under moderate thermophilic conditions in the presence of chloride ion - Bobadilla-Fazzini, Roberto A (AMB Express, 2014)
Currently more than 90% of the world’s copper is obtained through sulfide mineral processing. Among the copper sulfides, chalcopyrite is the most abundant and therefore economically relevant. However, primary copper sulfide bioleaching is restricted due to high ionic strength raffinate solutions and particularly chloride coming from the dissolution of ores. In this work we describe the chalcopyrite bioleaching capacity of Sulfobacillus thermosulfidooxidans strain Cutipay (DSM 27601) previously described at the genomic level (Travisany et al. (2012) Draft genome sequence of the Sulfobacillus thermosulfidooxidans Cutipay strain, an indigenous bacterium isolated from a naturally extreme mining environment in Northern Chile. J Bacteriol 194:6327–6328). Bioleaching assays with the mixotrophic strain Cutipay showed a strong increase in copper recovery from chalcopyrite concentrate at 50°C in the presence of chloride ion, a relevant inhibitory element present in copper bioleaching processes. Compared to the abiotic control and a test with Sulfobacillus acidophilus DSM 10332, strain Cutipay showed an increase of 42 and 69% in copper recovery, respectively, demonstrating its high potential for chalcopyrite bioleaching. Moreover, a genomic comparison highlights the presence of the 2-Haloacid dehalogenase predicted-protein related to a potential new mechanism of chloride resistance in acidophiles. This novel and industrially applicable strain is under patent application CL 2013–03335. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13568-014-0084-1) contains supplementary material, which is available to authorized users.